PENGARUH LEADERSHIP, REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI DI PT. POS INDONESIA KABUPATEN SITUBONDO - Minullah, Minullah; Ediyanto, Ediyanto; Erniyanto, Moh. Viky (Growth, 2025)
This study aims (1) to determine the effect of leadership, reward and punishment partially effect on employee performance (2) to determine the effect of leadership, reward and punishment simultaneously influence on employee performance (3) to find out Among leadership. reward and the most dominant punishment influences employee performance. The method used is quantitative. The results of the research are multiple linear regression equation Y = 3,957E-16 + 0,328 X1 + 0,139 X2 + 0,641 X3 + e. partially significant positive effect on leadership with a t-value greater than t table (7,269) > (2,032) or sig α 0,000 < 0.05, reward indicates a t-count greater than t table (2,439) > (2,032) or sig α 0.020 < 0.05, punishment shows that the value of t is greater than table (2,383) > (2,032) or sig α 0,023 < 0.05. Simultaneously leadership, reward and punishment have an effect on employee performance with a calculated F value of 44,309 values greater than the F table of 2.88 or an F count of 44,309 > F table of 2.88. The variable that has the most dominant influence in this study is the leadership with a value of 7,269. R2 value of the leadership, reward and punishment variables of 79,6% and the remaining 20,4% is influenced by other factors not included in the study